Childhood Quarantine: Pagsusuri sa Akdang Ang Misteryo sa Patong-Patong na Damit ni Hulyan Bilang Radikal na Kuwentong Pambata sa Panahon ng Pandemya sa Pilipinas (Childhood Quarantine: Literary Analysis of "Ang Misteryo sa Patong-patong na Damit ni Hulyan" as Radical Children Story in Time of Philippine Pandemic) - Teodoro, Alyssa (Social Sciences and Development Review, 2023)
Literature became a medium, in any form and kind as a reflection of society at a particular time. One of these is children’s literature, a literary work whose reader is a child or children. Children’s literature has also become an instrument to show children as well as adults the real situation of the world in which they live. Radical children’s literature also known as progressive children’s literature encourages the reader to participate in social change. This study wants to present a radical children’s story during the pandemic and a heinous crime happening in some homes in the Philippines. By using textual analysis as its methodology, The Mystery Behind Hulyan’s Layered Clothes, is a radical children’s story published during the pandemic. The study wants to show the intensifying Online Sexual Exploitation of Children in the Philippines and the dark experience of a child as a victim. Some objective situations of the Filipino children during the pandemic will also be discussed to raise awareness in inventing radical children’s literature in the future.